Development and evaluation of 3D-printed tumor palpation models for surgical training and patient education - Haruna Katori; Atsushi Fushimi; Soichiro Fujimura; Rei Kudo; Makiko Kamio; Hiroko Nogi (3D Printing in Medicine)
Abstract Breast cancer screening is implemented as part of governmental healthcare policy in many countries. While breast imaging tests contribute to reducing mortality, some breast cancers may emerge between these screenings. Consequently, it is crucial for women to be vigilant about any changes in their breasts to facilitate the early detection of breast cancer. Recently, the application of 3-dimensional printing technology in the medical field has expanded, including uses in medical imaging and surgical training. In this study, we developed 3D-printed palpation models for breast tumor detection and surveyed seven surgeons specializing in breast care to evaluate the usability of the models. As a result of the survey, we created a model that obtained a maximum mean rating of 7.1(maximum rating 10, minimum rating 3) on the item 'How accurately does the model simulate the feel of a real tumor?' on a scale from 1 to 10. Although there is some variation in the average value, through this study, we found that it is possible to create a model that is quite close to the actual tumor depending on the materials and shape of the models. Our findings demonstrated the potential use of personalized models both in medical trainee and patient education.